Ethical responses to modern clinical trials on human subjects: a comparative perspective - Hashi, Abdurezak Abdulahi; Abdul Razak, Tariq (Kulliyyah of Medicine and IIUM Press, 2018)
With the modern advances and technological breakthroughs in biomedicine, scientific experiments involving human subjects had increased. Since the American gynecologist Marion Sims (d.1883), who conducted a scientific research on some selected African women suffering from prolapsed uterus disease, or American physician Walter Reed’s (d.1902) team who gave germs of yellow fever to 22 human subjects to test if fever is transmitted by particularly mosquito species, as well as the Tuskegee Syphilis Study that was conducted from 1932 until 1972, or the scientific experiments conducted by Nazis of Germany on large numbers of prisoners, clinical trials on human subjects have become part of the scientific activities. These and many other scientific experiments conducted on human subjects had shown the extent of potential threats of unregulated scientific experiments on human life. Serious moral and legal concerns are then raised towards the morality of these activities. These concerns covered four major areas; safety, sanctity of the human body, consent and validity of experiment. This paper uses textual and analytical methods and aims to review Muslim jurists’ opinions on the permissibility of conducting clinical researches that uses human subjects. The opinions of the Muslim jurists are then compared to that of bioethical codes and declarations such as the Nuremberg Code, coined in (1947) and the Helsinki Declaration that was formulated by World Medical Organization in 1964. Fiqh and legal literature on this subject is exposed, and the moral contents of such writings are analyzed. The study is expected to come up with a comparative account of conventional and Islamic responses to modern clinical trials on human subjects.